Contribution of M-1 and M-2 muscarinic receptor subtypes to convulsions in fasted mice treated with scopolamine and given food - AYDIN OMAY, BANU; CABADAK, HÜLYA; GÖREN, MEHMET ZAFER; BACANAK, MERVE (ELSEVIER SCIENCE BV, 2019)
Treatment of fasted mice and rats with the nonselective muscarinic antagonist, scopolamine or atropine, causes convulsions after food intake. This study evaluated the effect of fasting on the expression of M-1 and M-2 muscarinic receptors in the brain regions, the relationship between receptor expression and seizure stages, and the muscarinic receptor subtype which plays a role in the occurrence of convulsions. Mice were grouped as allowed to eat ad lib (fed) and deprived of food for 24 h (fasted). Fasted animals developed convulsions after being treated with scopolamine (60%) or the selective M-1 receptor antagonist pirenzepine (10 mg/kg; 20% and 60 mg/kg; 70%) and given food. Fasting increased expression of M-1 receptors in the frontal cortex and M-2 receptors in the hippocampus, but produced no change in the expression of both receptors in the amygdaloid complex. Food intake after fasting decreased M-1 receptor expression in the frontal cortex and M-1 and M-2 receptor expression in the hippocampus. Seizure severity was uncorrelated with muscarinic receptor expression in the brain regions. Taken together, these findings provide evidence for the role of M-1 muscarinic receptor antagonism and fasting-induced increases in M-1 and M-2 expression possible underlying mechanism in the occurrence of convulsions in fasted animals.
Keywords: Fasting; Convulsion; M-1 muscarinic receptor expression; M-2 muscarinic receptor expression; Scopolamine; Pirenzepine; Food intake; ACETYLCHOLINE-RELEASE; CHOLINERGIC MODULATION; BASOLATERAL AMYGDALA; CEREBRAL-CORTEX; SEIZURES; BRAIN; M1; LOCALIZATION; EXPRESSION; NUCLEUS